Teachers as Meaning Makers in Empathetic Reading Sessions: Toward More Emotional and Holistic Literature Pedagogy - Kauppinen, Merja; Aerila, Juli-Anna (Scandinavian University Press, 2025)
Purpose: This study explores interactive poetry therapy as a method for empathetic reading in holistic, emotional literature education. Design: Five experienced teachers participated in a descriptive case study by attending interactive empathetic reading sessions during in-service education. The participants, inspired by an extract from a novel, wrote personal stories and presented them for group discussions. Methodology: The data, consisting of audio recordings of the dialogues and the researchers’ associated notes, were analysed via thematic content analysis. Three main themes, which are presented under the headings: Story level; narrative meanings; Individual level; emotions relating to storytelling moments; and Communal level; issues of welfare and self-care. Findings: The results indicated that the writers’ personal stories and the group dialogues based on them prompted the participants to reflect on their own experiences and emotions, and prompted them to examine ethically challenging issues in the teaching profession. Originality: The study of empathetic reading in teachers’ in-service education provide more understanding of possibilities for teachers to increase their knowledge of the value of stories and narratives.